Cryptochromes in mammals: a magnetoreception misconception? - Zhang, Li; Malkemper, E. Pascal (Frontiers in Physiology, 2023)
Cryptochromes are flavoproteins related to photolyases that are widespread throughout the plant and animal kingdom. They govern blue light-dependent growth in plants, control circadian rhythms in a light-dependent manner in invertebrates, and play a central part in the circadian clock in vertebrates. In addition, cryptochromes might function as receptors that allow animals to sense the Earth’s magnetic field. As cryptochromes are also present in mammals including humans, the possibility of a magnetosensitive protein is exciting. Here we attempt to provide a concise overview of cryptochromes in mammals. We briefly review their canonical role in the circadian rhythm from the molecular level to physiology, behaviour and diseases. We then discuss their disputed light sensitivity and proposed role in the magnetic sense in mammals, providing three mechanistic hypotheses. Specifically, mammalian cryptochromes could form light-induced radical pairs in particular cellular milieus, act as magnetoreceptors in darkness, or as secondary players in a magnetoreception signalling cascade. Future research can test these hypotheses to investigate if the role of mammalian cryptochromes extends beyond the circadian clock.